FOSTERING STUDENTS' INTEREST IN MATHEMATICS LEARNING WITH THE UTILIZATION OF ETHNOMATHEMATICS THROUGH MAKKUDENDENG TRADITIONAL GAME - Andi Aras; Fawziah Zahrawati (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
Interest in learning is one important factor that determines student success in learning. Low student interest in learning is associated with their ability to master the concept of summing whole numbers. This study aims to foster students' interest in learning mathematics through makkudendeng traditional game. The research method is design research starting from the preliminary design, design experiment, and retrospective analysis. The research subjects were students in grade II primary school. The results of this study conclude that the makkudendeng traditional game, which is used as a learning resource in learning the addition of whole numbers, has relevance to the indicators of learning interest, which include: pleasure in learning, interest in learning, attention, and involvement in learning. It is because students learn while playing. So, the makkudendeng traditional game can be a solution to foster students' interest in learning mathematics.